Analisis Kualitas Udara Parameter Deposisi Basah dan Deposisi Kering di Sorong Tahun 2022 - Syafaati, Ayu Diah; Yuni Kartika (LRI Universitas Muhammadiyah Sorong, 2023)
Acid deposition is a phenomenon of air pollution that is mostly associated with energy activities that emit acidic pollutant compounds into the atmosphere. Acid deposition is one of the effects of air pollution. Observation of air quality in Sorong City is needed to determine the level of air pollution that occurs due to natural factors and anthropogenic activities. Observation of acid deposition in Sorong City was carried out with two parameters, namely wet deposition and dry deposition. Observation of wet deposition using chemical measurements of rainwater in the form of pH, Conductivity, and Mineral Ion Concentration. Observation of dry deposition using SPM Particulate and Passive Gas (SO2 and NO2) parameters. The results show that the level of acidity (pH) of rainwater in Sorong City during 2022 is included in pH category of acidic rainwater that tends to be neutral. Meanwhile, the result of conductivity value is 2.2 – 50.9 µS/cm. The chemical composition in rainwater in Sorong City is dominated by chloride ions, sulfate ions, potassium ions and sodium ions, where the number of anions accounts for 59% of the total ions present in rainwater, and cations contribute 41%. During January to December 2022, daily SPM concentrations were in the range of 8.63 - 96.24 µg/m3. Based on the value of the quality standard, both daily and yearly, SPM value is still far below the applicable threshold value. The results of SO2 and NO2 measurements in Sorong City also show that concentration values are still below the air quality standard values.